The seven mountains of Thomas Merton - Mott, Michael, 1930- (Boston : Houghton Mifflin, 1984)
A biography of the Catholic priest who wrote "The Seven Storey Mountain."
Includes index.
Bibliography: p. [655]-674.
Young Adult
Young Adult
Wilson's Public Library
Booklist
Keywords: Merton, Thomas, -- 1915-1968.; Merton, Thomas, -- 1915-1968.; Trappists -- United States -- Biography; Priests -- Biography